Building integrated solar thermal systems – a new era of renewables in buildings - Kalogirou, Soteris A. (My University, 2016)
Buildings’ in EU consume 40% of the primary energy requirements. This is the main reason the Energy Performance of Buildings Directive was implemented whereas the recast of the Directive, specifies that the buildings erected after 2020 should be of nearly zero energy consumption, a requirement that assumes extensive use of renewables. This new role of renewables implies that in addition to photovoltaics, solar thermal systems (STS) will also have a main role to play. The primary use of STS is to meet the building thermal loads, after the traditional standard building energy saving measures are applied, like thermal insulation, double glazing, etc. STS are typically mounted on building roofs as add-on components with no attempt to incorporate them into the building envelope. In this way aesthetic challenges, space availability issues and envelope integrity problems need to be considered. The purpose of this paper is to give a survey of possible applications of STS integration on the building roofs and façades. Details of some projects already under development are also presented.
Keywords: Building integration; Building performance; Solar thermal systems; Flat-plate collectors